The Lingual and Pragmatic Characteristics of Occasionalisms in the American Media Discourse - Siredzhuk, O. (Journal of Vasyl Stefanyk Precarpathian National University, 2016)
In the article, the notion of an occasionalism was studied; its place and role in the media discourse were outlined. While analyzing occasionalisms according to the theory of relevance by D. Sperber and D. Wilson, the inferential processes in the interpretation of utterances containing occasionalisms were traced. Thanks to conducted analysis, the meaning of occasional units was inferred, the pragmatic characteristics of these units were described and the effects, which they produce in media texts, were singled out